Cholix toxin, an eukaryotic elongation factor 2 ADP‐ribosyltransferase, interacts with Prohibitins and induces apoptosis with mitochondrial dysfunction in human hepatocytes. (14th May 2019) - Yahiro, Kinnosuke; Ogura, Kohei; Terasaki, Yasuhiro; Satoh, Mamoru; Miyagi, Satoru; Terasaki, Mika; Yamasaki, Eiki; Moss, Joel
Abstract: Vibrio cholerae produced‐Cholix toxin (Cholix) is a cytotoxin that ADP‐ribosylates eukaryotic elongation factor 2, inhibiting protein synthesis, and inducing apoptosis. Here, we identified prohibitin (PHB) 1 and 2 as novel Cholix‐interacting membrane proteins in immortalised human hepatocytes and HepG2 cells by Cholix immunoprecipitation assays. The expression level of PHB1 was decreased by Cholix after a 12hr incubation. Cholix‐induced poly (ADP‐ribose) polymerase (PARP) cleavage was significantly enhanced in PHB (PHB1 or PHB2) knockdown cells. In contrast, transiently overexpressed PHB in hepatocytes attenuated Cholix‐induced Bax/Bak conformational changes and PARP cleavage. In addition, Cholix‐induced reactive oxygen species production and accumulation of fragmented mitochondria were enhanced in PHB‐knockdown cells. Furthermore, Cholix induced activation of Rho‐associated coiled coil‐containing protein kinase 1 (ROCK1), which was enhanced in PHB‐knockdown cells, followed by actin filament depolymerisation and accumulation of tubulin in the blebbing cells. Inhibition of ROCK1 by siRNA or its inhibitor suppressed Cholix‐induced PARP cleavage and reactive oxygen species generation. Our findings identify PHB as a new protein that interacts with Cholix and is involved in Cholix‐induced mitochondrial dysfunction and cytoskeletal rearrangement by ROCK1 activation during apoptosis.